Pengembangan Media Pembelajaran Interaktif Berbasis Problem Based Learning (PBL) Berbantuan Android Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VII SMP Negeri 1 Sosopan - Aidatul Ira Harahap; Irwan Irwan; Edwin Musdi; Ali Asmar (Universitas PGRI Madiun, 2021)
This research is motivated by the low mathematical problem solving ability of junior high school students. This study aims to produce a valid, practical, and effective Android-assisted problem-based interactive learning media to facilitate mathematical problem solving abilities. This research is a development research carried out with the Plomp development model. The Plomp development model consists of three stages, namely preliminary investigation, prototyping stage, and assessment phase. The research was conducted at SMPN 1 Sosopan with the research subjects being material experts, linguists and educational technology experts as well as seventh grade students at SMPN 1 Sosopan. Data collection instruments in the form of interviews, documentation, questionnaires and test questions. The data obtained were analyzed using qualitative and quantitative data analysis techniques. The results showed that the Android-assisted problem-based interactive mathematics learning media developed was classified as very valid (89,11% for lesson plans and 87,73% for media) and very practical, respectively 87% and 86,85%. (for lesson plans and small group media) 88,1% and 88,02% (for lesson plans and large group media). Meanwhile, based on the test results of the mathematical problem solving ability test, it was found that 81,5% of students met the criteria for the success of the mathematical problem solving ability test > 80%, meaning that the interactive learning media based on Android-assisted problem-based learning was very effective on mathematical problem solving abilities.